Mode of action of silver-based perovskite against Gram-negative bacteria - Fereshteh Fani; Cyrus Talebpour; Philippe Leprohon; Hossein Salimnia; Houshang Alamdari; Marc Ouellette (Microbiology Spectrum)
ABSTRACT Although silver is known for its antibacterial activity, its exact mode of action remains unclear. In our previous work, we described AgNbO3 nanoparticles (AgNbO3 NPs) prepared using a ceramic method, followed by high-energy and low-energy ball-milling processes, which exhibited antimicrobial activity with negligible release of Ag+ in deionized water. Here, we investigated thoroughly the mode of action of these AgNbO3 NPs against Escherichia coli. Drastic morphological changes in E. coli were observed after their exposure to AgNbO3 NPs. In addition to cellular damage, AgNbO3 NPs induced the production of reactive oxygen species and lipid peroxidation, likely following the release of small amounts of Ag+. This was concluded from the characterization of mutants resistant to AgNbO3 NPs that showed cross-resistance to AgNO3, impaired reactive oxygen species production and lipid peroxidation, and harbored a key mutation in a two-component regulatory system regulating an Ag+ efflux pump. We calculated, however, that the quantity of Ag+ released from AgNbO3 NPs is not sufficient by itself to lead to bacterial death. We propose that bacterial contact with the AgNbO3 NPs in combination with Ag+ release is necessary for the mode of action of AgNbO3 NPs.IMPORTANCESilver is known for its antibacterial activity, but its exact mode of action remains unclear. Here, we investigated thoroughly the mode of action of AgNbO3 nanoparticles against Escherichia coli. Our data suggest that AgNbO3 nanoparticles have dual effects on the cell and that both are required for its lethal action.